The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12935-022-02551-9
|View full text |Cite
|
Sign up to set email alerts
|

Functions and underlying mechanisms of miR-650 in human cancers

Abstract: MicroRNAs (miRNAs) are one type of noncoding RNAs that interfere with mRNA translation to downregulate gene expression, which results in posttranscriptional gene silencing. Over the past two decades, miRNAs have been widely reported to impact the progression of malignant tumours by interfering with cancer initiation and progression; therefore, miRNAs represent potential new diagnostic and therapeutic tools. miR-650 is a newly identified miR, and increasing studies have demonstrated that miR-650 plays critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…These include gastric cancer, oral cancer, prostate cancer, and anaplastic thyroid cancer. 34 However, previous studies have reported that in CRC, miR‐650 not only inhibits tumor growth but also promotes tumor progression. For example, miR‐650 was downregulated in CRC as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include gastric cancer, oral cancer, prostate cancer, and anaplastic thyroid cancer. 34 However, previous studies have reported that in CRC, miR‐650 not only inhibits tumor growth but also promotes tumor progression. For example, miR‐650 was downregulated in CRC as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that miR‐650 can function as a tumorigenic miRNA in various solid tumors. These include gastric cancer, oral cancer, prostate cancer, and anaplastic thyroid cancer 34 . However, previous studies have reported that in CRC, miR‐650 not only inhibits tumor growth but also promotes tumor progression.…”
Section: Discussionmentioning
confidence: 99%